Fatal descending necrotising mediastinitis. Issue 1 (20th January 2004) - Bulut, M; Balcı, V; Akköse, Ş; Armağan, E
Abstract : Descending necrotising mediastinitis rarely develops and this variety of mediastinitis is a highly lethal disease. A case is reported of descending necrotising mediastinitis caused by an odontogenic infection. The importance is emphasised of prompt diagnosis and aggressive surgical mediastinal drainage for the survival of these patients. Most acute mediastinal infections result from oesophageal perforation, either secondary to oesophagoscopy or tumour erosion. Mediastinitis occasionally develops as descending necrotising mediastinitis originating from the complications of cervical or odontogenic infections. Descending necrotising mediastinitis usually has a fulminant course, leading commonly to sepsis and death.